Seven years' experience with antilymphoblast globulin for renal transplantation from cadaver donors. - Najarian, J S (1976)
Antibody of the IgGab type can be isolated from horses immunized with cultured human lymphoblasts plus complete Freund's adjuvant. The essential steps for the production of a safe, potent anti-human lymphoblast globulin (ALG) are: A) the use of early bleedings after immunization to reduce the titer of antibodies which react with red blood cells and platelets; B) careful absorption with human red blood cell stroma and platelets; C) stabilization with non-crystalline silica dioxide; D) chromatography through QAE sephadex to remove pyrogens, microaggregates and possible inhibitors of ALG activity; E) careful safety testing in animals for toxicity and pyrogenicity; and F) testing in vitro for sterility. Such a purified horse ALG (IgGab) can be administered safely intravenously to patients to supplement a standardized immunosuppressive regimen incorporating azathioprine and prednisone. Under these circumstances, allergic reactions are very rare, antibodies to horse IgG do not develop, skin tests to horse IgG remain negative, and immune elimination of circulating horse IgG from the human circulation cannot be demonstrated. The overall results of ALG patient survival and transplant function after 184 consecutive first cadaver transplants at the University of Minnesota demonstrate a statistically significant improvement in both parameters accompanying increases in ALG dose while rigidly utilizing standardized doses of azathioprine and prednisone. There is a significant reduction in the number of grafts lost to rejection; significant reduction in the number of rejection episodes; significant delay in the onset of rejection episodes; but there is no increase in septic loss of patients or kidneys. These efforts could be seen in the gross data or when subgroups controlling for patient age, tissue typing were analyzed. Excluding patients at high risk did not alter the results. The beneficial effects of ALG were particularly striking in good matches. In the highest doses, ALG may be dangerous for older patients with poor matches who develop an increased incidence of septic loss of kidney and/or life. Thus, ALG appears to be a useful adjunct in the early management of cadaver transplants by reducing the incidence and frequency of rejection episodes. The dose should probably be reduced in the older patients who receive kidneys from badly mismatched donors. One cannot conclude from this study that ALG manufactured in other centers by this or other techniques, will accomplish the same results since the multiplicity of factors involved in the success and failure of transplants must be controlled so that the influence of intravening variables in the assessment of ALG effectiveness can be assessed.